A new species of cyprinoid fish from the Tana River, Kenya (Actinopterygii: Danionidae) - Bart, Henry L. Jr.; Schmidt, Ray C.; Nyingi, Wanja Dorothy; Gathua, Joseph (Zootaxa, 2019)
Sampling of streams in the middle reaches of the Tana River Basin in Meru National Park, Kenya, from 2010 to 2012 for an NSF-funded International Research Experiences for Students (IRES) project, resulted in the capture of a number of specimens of what were first thought to be Neobola fluviatilis.  On closer examination the specimens were determined to represent a distinct species, endemic to the Tana River basin, which is herein formally described. The new species is readily diagnosed from N. fluviatilis by higher counts of lateral line, pre-dorsal, and caudal peduncle circumferential scales, higher numbers of pectoral rays, lower numbers of anal fin rays, and a shorter anal-fin base length.